32. NUTRITIONAL STATUS OF CHILDREN UNDER 24 MONTHS OLD AT THE GENERAL AND OCCUPATIONAL CLINIC, INSTITUTE OF PREVENTIVE MEDICINE AND PUBLIC HEALTH IN 2023-2024 (Vietnam Journal of Community Medicine, 2024)
Objects, methods and objectives: This cross-sectional study was conducted on 354 children under 24 months in the General and Occupational Clinics, Institute of Preventive Medicine and Public Health in 2023-2024 to: (1) Assess the nutritional status of children visited the clinics; and (2) Describe the associated factors of the children’s nutritional status.Results: The rates of children under 24 months of age suffering from malnutrition in the forms of underweight, stunting and wasting are 1.4%, 7.3% and 2.8% respectively. The prevalence of underweight and stunting in the children aged 18-23 months was statiscally significant higher than the other age groups (p < 0,05). Some associated factors determined are birth weight < 2500g, pregnancy at the delivery ≤ 37 weeks, mothers ate less during the pregnancy (p < 0.05 in all comparisons).Conclusion: The prevalence of malnutrition of children under 24 months of age was low (1.4-7.3%). However, in the age group of 18-23 months, the malnutrition rate is still high (28.2%). Birth weight, gestational week of birth, and maternal nutrition during pregnancy are statistically significant factors related to the nutritional status of children.
Keywords: Malnutrition; children under 24 months; stunting; birth weight; pregnant and lactating women